2019
DOI: 10.1186/s12885-019-6010-9
|View full text |Cite
|
Sign up to set email alerts
|

Use and effectiveness of pegfilgrastim prophylaxis in US clinical practice:a retrospective observational study

Abstract: Background: Febrile neutropenia (FN) is a serious complication of myelosuppressive chemotherapy. Clinical practice guidelines recommend routine prophylactic coverage with granulocyte colony-stimulating factor (G-CSF)-such as pegfilgrastim-for most patients receiving chemotherapy with an intermediate to high risk for FN. Patterns of pegfilgrastim prophylaxis during the chemotherapy course and associated FN risks in US clinical practice have not been well characterized. Methods: A retrospective cohort design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Among women with breast cancer receiving a low-risk regimen (AC: doxorubicin þ cyclophosphamide [conventional-dose]), however, no such benefits were reported. One other recent study, which comprised separate analyses of commercially insured patients and Medicare patients, respectively, documented the effectiveness of pegfilgrastim prophylaxis among patients with non-metastatic breast cancer or NHL receiving chemotherapy with an intermediate/high-risk for FN 79 . In the first analysis, which utilized data from two large private healthcare claims databases (2010-2016), FN odds in cycle 1 were significantly higher among patients not receiving prophylaxis versus those receiving pegfilgrastim prophylaxis (FN broad definition: OR ¼ 2.6, 95% CI 2.3-2.8; FN narrow definition: OR ¼ 4.2, 95% CI 3.8-4.7).…”
Section: Use Of Pegfilgrastim In Us Clinical Practicementioning
confidence: 99%
“…Among women with breast cancer receiving a low-risk regimen (AC: doxorubicin þ cyclophosphamide [conventional-dose]), however, no such benefits were reported. One other recent study, which comprised separate analyses of commercially insured patients and Medicare patients, respectively, documented the effectiveness of pegfilgrastim prophylaxis among patients with non-metastatic breast cancer or NHL receiving chemotherapy with an intermediate/high-risk for FN 79 . In the first analysis, which utilized data from two large private healthcare claims databases (2010-2016), FN odds in cycle 1 were significantly higher among patients not receiving prophylaxis versus those receiving pegfilgrastim prophylaxis (FN broad definition: OR ¼ 2.6, 95% CI 2.3-2.8; FN narrow definition: OR ¼ 4.2, 95% CI 3.8-4.7).…”
Section: Use Of Pegfilgrastim In Us Clinical Practicementioning
confidence: 99%
“…G-CSFs increase the production (i.e., differentiation and proliferation) and activity of neutrophils, which improve immune defense against infection and reduce the risk of FN [12][13][14]. Despite available evidence that prophylactic G-CSF is associated with a lower risk of FN, sustained chemotherapy dose intensity, and reduced mortality [15], several studies have reported that many patients for whom prophylaxis is recommended do not receive it in US clinical practice [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The prophylactic effect of pegfilgrastim has not been fully evaluated throughout the cycles of standard R-CHOP in DLBCL patients as previous studies included heterogeneous disease groups (NHLs), diverse regimens (CHOP, R-CHOP, and others), use of pegfilgrastim only in the first cycle, or mixed use of G-CSF or pegfilgrastim [9,10,[22][23][24]. In real-world practice, primary prophylaxis is not fully performed [13]. As pegfilgrastim prophylaxis has been available in Korea since 2014, we were able to compare the incidence of FN and treatment outcomes of DLBCL patients treated with R-CHOP between two cohorts collected during different time periods.…”
Section: Discussionmentioning
confidence: 99%
“…CANCER RESEARCH AND TREATMENT (CRT) 13 Korean Cancer Association This article is protected by copyright. All rights reserved.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%